2015
DOI: 10.1111/adb.12286
|View full text |Cite
|
Sign up to set email alerts
|

KAT2Bpolymorphism identified for drug abuse in African Americans with regulatory links to drug abuse pathways in human prefrontal cortex

Abstract: Drug abuse is a common and heritable set of disorders, but the underlying genetic factors are largely unknown. We conducted genome-wide association studies of drug abuse using 7 million imputed single nucleotide polymorphisms (SNPs) and insertions/deletions in African Americans (AAs; n=3,742) and European Americans (EAs; n=6,845). Cases were drawn from the Urban Health Study of street-recruited people, who injected drugs and reported abusing opioids, cocaine, marijuana, stimulants, and/or other drugs 10 or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…However, based on the prevalence of cocaine dependence (about 1.1%), the probability of false negative results due to this effect is low, and similar controls were used in other GWAS of drug addiction (Johnson et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…However, based on the prevalence of cocaine dependence (about 1.1%), the probability of false negative results due to this effect is low, and similar controls were used in other GWAS of drug addiction (Johnson et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Next, GWAS of people who inject drugs vs. controls, revealed an African American-specific association for the intronic SNP rs9829896 in the lysine acetyltransferase gene ( KAT2B ; P=4.6×10 −8 , N=3,742), which replicated in an independent dataset (P=0.0016, N=755) [119]. Follow-up analyses in postmortem human PFC implicated rs9829896 as a cis -eQTL SNP, specifically in African Americans, for KAT2B and other genes in KAT2B -containing pathways, including OPRM1 and the CREB binding protein ( CREBBP ) genes [119] that have been highlighted in prior SNP- or pathway-based analyses of opioid phenotypes [109, 112, 116].…”
Section: Gwas For Illicit Drugs Combinedmentioning
confidence: 99%
“…Given the high levels of co-morbidity across drugs of abuse and the plausible shared heritability underlying susceptibility to developing addiction in general, three GWAS have combined cases addicted to any illicit drug [18, 118, 119]. Two of these GWAS reported genome-wide significant and replicable associations.…”
Section: Gwas For Illicit Drugs Combinedmentioning
confidence: 99%
“…Johnson et al [60] conducted a GWAS of drug abuse in a sample that included 3,742 AA and 6,845 EA subjects. The majority of cases were recent opioid (>60%) and cocaine (>25%) users, while the control subjects included unassessed population controls and subjects that were negative for SUDs based on an assessment that used DSM-IV criteria.…”
Section: Gwas Of Co-occurring Sudsmentioning
confidence: 99%
“…No significant effects were detected in the EA sample. In interesting follow-up studies, Johnson et al [60] showed that rs9829896 was associated with KAT2B mRNA expression in postmortem brains from AA subjects, but not EA subjects. A KAT2B -centric network of 20 proteins that share pathways, physical interactions and protein domains was predicted.…”
Section: Gwas Of Co-occurring Sudsmentioning
confidence: 99%